Celebrating Canada. - Blake, Raymond Benjamin; Hayday, Matthew, 1977- (University of Toronto Press, 2018)
Popular and government-funded anniversaries and commemorations, combined with national symbols, play significant roles in shaping how we view Canada, and also provide opportunities for people to challenge the pre-existing or dominant conceptions of the country. Volume 2 of Celebrating Canada continues the scholarly debate about commemoration and national identity. Raymond B. Blake and Matthew Hayday bring together emerging and established scholars to consider key moments in Canadian history when major anniversaries of Canada's political, social, or cultural development were celebrated. The contributors to this volume capture the multiple and multi-layered meanings of belonging in the Canadian experience, investigate various attempts at shaping and re-shaping identities, and explore episodes of groups resisting or participating in the identity-formation process. By considering the small voices and those on the margins of Canada's many commemorative anniversaries, the contributors to Celebrating Canada reveal how important it is to think not only about anniversary moments but also about what they can tell us about our history and the shifting function of nationalism.